The influence of interfacial tensile strain on the charge transport characteristics of MoS2-based vertical heterojunction devices. Issue 40 (30th September 2016) - Huang, Fu; Cho, Byungjin; Chung, Hee-Suk; Son, Seung Bae; Kim, Jung Han; Bae, Tae-Sung; Yun, Hyung Joong; Sohn, Jung Inn; Oh, Kyu Hwan; Hahm, Myung Gwan; Park, Jung Hee; Hong, Woong-Ki
Abstract : Charge transport characteristics of MoS2 -based vertical heterojunctions. Abstract : We demonstrate the charge transport characteristics of MoS2 -based vertical heterojunction devices through the formation of interfacial strain. Atomically thin MoS2 bilayers were directly synthesized on a p-type Si substrate by using chemical vapor deposition to introduce an interfacial tensile strain in the vertical heterojunction diode structure, which was confirmed by Raman, X-ray and ultraviolet photoelectron spectroscopy techniques. The electrical and optoelectronic properties of the heterojunction devices with the as-grown MoS2 (A-MoS2 ) on p-Si were compared with those of transferred MoS2 (T-MoS2 )/p-Si devices. To clearly understand the charge transport characteristics induced by the interfacial tensile strain, the Fowler–Nordheim (FN) analysis of the electrical properties of the diode devices was conducted with the corresponding energy band diagrams. All of the fabricated MoS2 -based vertical diodes exhibited clearly rectifying behaviors, but the photoresponse properties of the A-MoS2 -based and T-MoS2 -based heterojunctions exhibited distinct differences. Interestingly, we found that the tunneling barrier heights of the A-MoS2 -based heterojunction devices were relatively higher than those of the T-MoS2 -based devices and were almost the same before and after illumination due to the interfacial tensile strain, whereas those of the T-MoS2 -based devices were lowered after illumination. Our study will help further understand the charge transport properties of 2D material-based heterojunction devices in the presence of interfacial strain, ultimately enabling the design of electronic and optoelectronic devices with novel functionalities.